INFORMATION SYSTEM DATA AND TRANSACTION DATA SUPPLIERS IN THE PROCUREMENT PROCESS IN PT GRASFINDO - Angga Ardiansyah; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2003)
PT Grasfindo is developing its business in the field of general trading (procurement office), which at this company processes transaction data of suppliers and information on the procurement of goods are still processed manually in the input, editing, printing to produce a report. Application programming using Microsoft Visual Basic 6.0 forms in form, would simplify the operational or administrative staff to do the inputting editing, printing, either from a data supplier data and transaction data, and assisted with Microsoft Access 2000 database applications to store recod- records and fields - field data .. Implementation of the program application of procurement processes in PT Grasfindo quite good and satisfactory in terms of receiving information quickly and accurately in order for decision making by the leadership.